Novel apexification method in a non-vital tooth with an open apex: a case report. - Hamid Razavian; Alireza Haerian; Hamid Mosleh (Tehran University of Medical Sciences, 2014)
Many materials have been introduced for apexification each having their own advantages and disadvantages. This case report aims to present a new method of apexification using a combination of deproteinized bovine bone mineral (DBBM) and enamel matrix derivative (EMD). After irrigating the canal of the maxillary right canine with 2.5 % sodium hypochlorite, a mixture of Bio-Oss and EMD was packed into the apical region for formation of an apical barrier and the canal was obturated by thermoplastic gutta percha technique with AH26 sealer; coronal seal was achieved by resin bonded composite. The size of the periapical lesion decreased significantly after 3, 6, 12 and 18-months. The patient had no radiographic signs or clinical symptoms at 24-month follow up and complete maturation of the apex and healing of the periapical bone were achieved.